Method for manufacturing a connection film and a connection structure

KR103020314B1Active Publication Date: 2026-09-16DEXERIALS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020237022379
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-23
Filing Date
2022-03-23
Publication Date
2026-09-16
Estimated Expiration
2042-03-23

Smart Images

  • Figure 112023072465553-PCT00005_ABST
    Figure 112023072465553-PCT00005_ABST
Patent Text Reader

Abstract

The present invention provides a method for manufacturing a connection film and a connection structure capable of obtaining excellent impact properties of a chip component by irradiation with laser light. The connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 0.2 to 60 MPa at a temperature of 30°C and a frequency of 200 Hz in a dynamic viscoelasticity test using an indentation test device. Additionally, it further contains a film-forming resin, a thermosetting resin, a curing agent, and an inorganic filler, and has a storage modulus of 0.1 GPa or more at a temperature of 30°C measured in a tensile mode in accordance with JIS K7244 after curing. By doing so, excellent impact properties of a chip component by irradiation with laser light can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a connection film for connecting chip components to a substrate and a method for manufacturing a connection structure. The present application claims priority based on Japanese Patent Application No. 2021-054274 filed in Japan on March 26, 2021 and Japanese Patent Application No. 2022-047405 filed in Japan on March 23, 2022, which is incorporated into the present application by reference. Background Technology

[0002] Recently, the development of Micro LEDs as next-generation displays for LCDs (Liquid Crystal Displays) and OLEDs (Organic Light Emitting Diodes) has been active. As a challenge for Micro LEDs, a technology called mass transfer, which mounts micro-sized LEDs onto a panel substrate, is required and is being researched in various places.

[0003] As a current main method of mass transfer, there is a method of transferring LEDs to the panel substrate side using a stamp material. FIG. 15 is a schematic diagram showing a stamp-type mass transfer. In the stamp method, as shown in FIG. 15A and FIG. 15B, an LED (101) is transferred from a transfer material (102) to a stamp material (103) and picked up, and as shown in FIG. 15C and FIG. 15D, the LED (101) is attached to a connection film (105) of a panel substrate (104). However, the method using a stamp material is not suitable for mass production because the pitch of the LED (101) depends on the pattern of the stamp material (103), the degree of freedom in design is low, the chip transfer rate is low, and it takes a considerable amount of time.

[0004] Therefore, what is currently receiving attention is a chip placement method using a laser (see, for example, Patent Documents 1 to 4). FIG. 16 is a schematic diagram illustrating a laser-based mass transfer. In the laser method, as shown in FIG. 16A and FIG. 16B, an LED (111) is transferred from a transfer material (112) to a release material (113) and picked up, and as shown in FIG. 15C, a laser light is irradiated onto the release material (113) to deposit the LED (111) onto a connection film (115) of a panel substrate (114). Chip transfer by the laser method has a high degree of design freedom and a very fast chip transfer takt compared to stamp material.

[0005] However, in the laser-based chip placement method, since the LEDs are ejected and struck on the panel substrate at a very high speed, there are cases where defects occur, such as the LEDs becoming misaligned, deformed, missing, or broken, as shown in Fig. 16D. Prior art literature

[0006] Japanese Published Patent Application No. 2020-096144 Japanese Published Patent Application No. 2020-145243 Japanese Published Patent Application No. 2019-176154 Japanese Published Patent Application No. 2020-053558 The problem to be solved

[0007] The present technology is proposed in consideration of such conventional conditions and provides a connection film capable of obtaining excellent impact properties of a chip component by laser light irradiation, and a method for manufacturing a connection structure. means of solving the problem

[0008] The connection film related to the present technology contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30 ℃ and a frequency of 200 Hz in a dynamic viscoelasticity test using an indentation test device.

[0009] A connection film substrate related to the present technology comprises the aforementioned connection film and a substrate having transmittance to laser light.

[0010] A method for manufacturing a connection structure related to the present invention comprises a chip component formed on a substrate having transmittance to laser light and a connection film on a wiring board facing each other, a bonding process in which a laser light is irradiated from the substrate side to bond the chip component onto the connection film, and a connection process in which the chip component and the wiring board are connected, wherein the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30 ℃ and a frequency of 200 Hz.

[0011] A method for manufacturing a connection structure related to the present invention comprises a connection film on the electrode surface of a chip component formed on a substrate having transmittance to laser light and a wiring board facing each other, a laser light irradiated from the substrate side to cause the chip component to be impacted onto the wiring board with the connection film interposed therebetween, and a connection process for connecting the chip component and the wiring board, wherein the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30 ℃ and a frequency of 200 Hz. Effects of the invention

[0012] According to the present technology, excellent shock absorption is obtained, so excellent impact resistance of chip components can be obtained. Brief explanation of the drawing

[0013] FIG. 1 is a cross-sectional view schematically showing a state in which a light-emitting element formed on a substrate and an anisotropic conductive film on a wiring substrate are facing each other. Figure 2 is an enlarged view showing a connection film on a wiring board and a light-emitting element facing each other. FIG. 3 is a cross-sectional view schematically showing a state in which a light-emitting element is transferred to a predetermined position on a wiring board and arranged by irradiating a laser light from the substrate side. FIG. 4 is a cross-sectional view schematically showing the state in which a light-emitting element is mounted on a wiring board. FIG. 5 is a cross-sectional view schematically showing an anisotropic conductive film formed on a substrate and a wiring substrate facing each other. FIG. 6 is a cross-sectional view schematically showing the state in which an anisotropic conductive film is transferred to a predetermined location on a wiring board and arranged by irradiating a laser light from the substrate side. FIG. 7 is a cross-sectional view schematically showing a state in which a light-emitting element formed on a substrate and an anisotropic conductive film on a wiring substrate are facing each other. FIG. 8 is a cross-sectional view schematically showing a state in which a light-emitting element is transferred to a predetermined position on a wiring board and arranged by irradiating a laser light from the substrate side. FIG. 9 is a cross-sectional view schematically showing a state in which a light-emitting element is mounted on a plate arranged at a predetermined position on a wiring board. FIG. 10 is a cross-sectional view schematically showing the state in which an anisotropic conductive film is transferred and arranged on a wiring board in electrode units by irradiating laser light from the substrate side. FIG. 11 is a cross-sectional view schematically showing a state in which a light-emitting element formed on a substrate and a reorganization transferred and arranged as electrode units on a wiring substrate are facing each other. FIG. 12 is a cross-sectional view schematically showing the state in which a laser light is irradiated from the substrate side to strike and arrange a light-emitting element on a corresponding electrode. FIG. 13 is a cross-sectional view schematically showing a state in which a light-emitting element is mounted on a reorganized wiring board. FIG. 14 is a cross-sectional view schematically showing a state in which a connection film formed on the electrode surface of a light-emitting element and a wiring substrate are facing each other. Figure 15 is a schematic diagram illustrating a stamp-type mass transfer. Figure 16 is a schematic diagram illustrating a laser-based mass transfer. Specific details for implementing the invention

[0014] Hereinafter, embodiments of the present technology will be described in detail in the following order with reference to the drawings.

[0015] 1. Connection film

[0016] 2. Method for manufacturing a connection structure

[0017] 3. First embodiment

[0018] 4. Second embodiment

[0019] <1. Connection Film>

[0020] The connection film related to the present embodiment contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30°C and a frequency of 200 Hz in a dynamic viscoelasticity test using an indentation test device. As a result, excellent shock absorption is obtained, thereby suppressing the occurrence of defects such as misalignment, deformation, breakage, or detachment of chip components, and improving the transfer rate of chip components by laser irradiation.

[0021] The rubber component is not particularly limited as long as it is an elastomer with high cushioning (shock absorption) properties, and specific examples include acrylic rubber, butadiene rubber, polyurethane resin (polyurethane-based elastomer), etc. Among these, it is preferable that the rubber component be acrylic rubber. The content of the rubber component may be 1 to 100 wt%, and when containing a thermosetting resin, a thermoplastic resin, etc., the content of the rubber component is preferably 1 to 20 wt%, more preferably 2 to 10 wt%.

[0022] The durometer A hardness of the connection film is 20 to 40, preferably 20 to 35, and more preferably 20 to 30. If the durometer A hardness is excessively high, the connection film becomes excessively hard, and defects such as deformation or breakage of the chip component tend to occur easily; if the durometer A hardness is excessively low, the connection film becomes excessively soft, and defects such as misalignment of the chip component tend to occur easily. The durometer A hardness of the connection film can be measured as rubber hardness (Japanese Industrial Standard JIS-A hardness) using durometer A in accordance with JIS K 6253.

[0023] The storage modulus at a temperature of 30°C and a frequency of 200 Hz for a dynamic viscoelasticity test using an indentation test device for a connection film is 60 MPa or less, preferably 30 MPa or less, and more preferably 10 MPa or less. If the storage modulus at a temperature of 30°C and a frequency of 200 Hz is excessively high, it cannot absorb the impact of a chip component ejected at high speed by laser irradiation, and the transfer rate of the chip component tends to decrease. The storage modulus at a temperature of 30°C and a frequency of 200 Hz can be measured by using an indentation test device, for example using a flat punch with a diameter of 100 μm, setting the target indentation depth to 1 μm, and sweeping a frequency range of 1 to 200 Hz.

[0024] In addition, the connection film further contains a film-forming resin, a thermosetting resin, a curing agent, and an inorganic filler, and it is preferable that the storage modulus at a temperature of 30°C, measured in a tensile mode in accordance with JIS K7244 after curing, be 100 MPa or higher, and more preferable that it be 2000 MPa or higher. If the storage modulus at a temperature of 30°C is excessively low, good conductivity is not obtained, and connection reliability tends to decrease. The storage modulus at a temperature of 30°C can be measured in a tensile mode using a viscoelastic tester (vibron) in accordance with JIS K7244, for example, under measurement conditions of a frequency of 11 Hz and a heating rate of 3°C / min.

[0025] The thermosetting binder containing a film-forming resin, a thermosetting resin, and a curing agent is not particularly limited, and examples include a thermoanionic polymerization resin composition comprising an epoxy compound and a thermoanionic polymerization initiator, a thermocationic polymerization resin composition comprising an epoxy compound and a thermocationic polymerization initiator, and a thermoradical polymerization resin composition comprising a (meth)acrylate compound and a thermoradical polymerization initiator. Furthermore, the term (meth)acrylate compound includes both acrylic monomers (oligomers) and methacrylate monomers (oligomers).

[0026] Among these thermosetting binders, it is preferable that the thermosetting resin contains an epoxy compound and the curing agent is a thermal cation polymerization initiator. This allows for rapid curing by heat by suppressing the curing reaction caused by laser light. Below, as a specific example, a thermal cation polymerization resin composition comprising a film-forming resin, an epoxy compound, and a thermal cation polymerization initiator will be described.

[0027] As for the film-forming resin, for example, it corresponds to a high molecular weight resin with an average molecular weight of 10,000 or more, and from the perspective of film-forming properties, it is preferable to have an average molecular weight of about 10,000 to 80,000. Various resins such as phenoxy resin, polyester resin, polyurethane resin, polyesterurethane resin, acrylic resin, polyimide resin, and butyral resin can be used as film-forming resins, and these may be used alone or in combination of two or more types. Among these, it is preferable to use phenoxy resin from the perspective of film-forming state and connection reliability. The content of the film-forming resin is preferably 20 to 50 parts by mass, more preferably 25 to 45 parts by mass or less, and even more preferably 35 to 45 parts by mass, based on 100 parts by mass of the total of the film-forming resin, thermosetting resin, curing agent, inorganic filler, and rubber component.

[0028] The epoxy compound is not particularly limited as long as it is an epoxy compound having one or more epoxy groups in its molecule; for example, it may be a bisphenol A type epoxy resin, a bisphenol F type epoxy resin, or a urethane-modified epoxy resin. Among these, a high-purity bisphenol A type epoxy resin may be preferably used. A specific example of a high-purity bisphenol A type epoxy resin is the product name "YL980" manufactured by Mitsubishi Chemical Corporation. The content of the epoxy compound is preferably 30 to 60 parts by mass, more preferably 35 to 55 parts by mass or less, and even more preferably 35 to 45 parts by mass, based on 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component.

[0029] As a thermal cation polymerization initiator, known thermal cation polymerization initiators for epoxy compounds may be employed. For example, known iodonium salts, sulfonium salts, phosphonium salts, ferrocenes, etc., may be used, which generate an acid capable of cation polymerizing a cation polymerization-type compound by heat. Among these, aromatic sulfonium salts that exhibit good potential with respect to temperature may be preferably used. A specific example of an aromatic sulfonium salt-based polymerization initiator is, for instance, the product name "SI-60L" manufactured by Sanshin Chemical Industry Co., Ltd. The content of the thermal cation polymerization initiator is preferably 1 to 15 parts by mass, more preferably 1 to 10 parts by mass or less, and even more preferably 3 to 8 parts by mass, based on 100 parts by mass of the total of the film-forming resin, thermosetting resin, curing agent, inorganic filler, and rubber component.

[0030] Inorganic fillers can be used to adjust the durometer A hardness, storage modulus at a frequency of 200 Hz, and storage modulus after curing of the thermosetting binder. As inorganic fillers, silica, talc, titanium oxide, calcium carbonate, magnesium oxide, etc., may be used. Inorganic fillers may be used alone or in combination of two or more types.

[0031] The content of the inorganic filler is preferably 1 to 20 parts by mass, more preferably 5 to 15 parts by mass or less, and even more preferably 8 to 12 parts by mass, based on 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component. When two or more types of inorganic fillers are used in combination, it is preferable that the total content of the inorganic fillers in the thermosetting binder is within the range described above. In particular, by having the content of the rubber component be 2 to 10 parts by mass with respect to 100 parts by mass of the total of the film-forming resin, thermosetting resin, curing agent, inorganic filler, and rubber component, and the content of the inorganic filler be 8 to 12 parts by mass with respect to 100 parts by mass of the total of the film-forming resin, thermosetting resin, curing agent, inorganic filler, and rubber component, it is possible to obtain the desired durometer A hardness, storage modulus at a frequency of 200 Hz, and storage modulus after curing.

[0032] In addition, as other additives to be incorporated into the thermosetting binder, silane coupling agents, diluent polymers, fillers, softeners, coloring agents, flame retardants, thixotropic agents, etc. may be incorporated as needed.

[0033] In addition, the connection film may additionally contain conductive particles and may be an anisotropic conductive film. As for the conductive particles, those used in known anisotropic conductive films may be appropriately selected and used. Examples include metal particles such as nickel, copper, silver, gold, palladium, and solder, and metal-coated resin particles in which the surface of resin particles such as polyamide and polybenzoguanamine is coated with a metal such as nickel or gold. This enables conductivity even when connection parts such as solder bumps are not formed on the chip component.

[0034] In addition, it is preferable that the conductive particles be arranged in a planar direction. By arranging the conductive particles in a planar direction, the particle plane density becomes uniform, which can further improve the transfer rate of the chip component by laser irradiation.

[0035] The particle size of the conductive particles is not particularly limited, but the lower limit of the particle size is preferably 2 μm or more, and the upper limit of the particle size is preferably 50 μm or less, for example, from the perspective of the capture efficiency of the conductive particles in the connection structure, and more preferably 20 μm or less. In addition, the particle size of the conductive particles can be a value measured by an image-type particle size distribution meter (for example, FPIA-3000: manufactured by Malvern Co.). This number is preferably 1,000 or more, preferably 2,000 or more. In addition, the particle face density of the conductive particles can be determined according to the electrode area of ​​the chip component, etc., and is, for example, 500 to 100,000 pcs / mm² 2 It can be done within the range of.

[0036] The lower limit of the thickness of the connection film may be, for example, equal to the particle diameter of the conductive particles, and preferably at least 1.3 times the particle diameter or at least 3 μm. In addition, the upper limit of the thickness of the connection film may be, for example, 20 μm or less or at least 2 times the particle diameter of the conductive particles. Furthermore, the connection film may be laminated with an adhesive layer or a pressure-sensitive adhesive layer that does not contain conductive particles, and the number of layers or the laminated surface may be appropriately selected according to the target or purpose. In addition, the insulating resin of the adhesive layer or pressure-sensitive adhesive layer may be the same as that of the connection film. The film thickness can be measured using a known micrometer or a digital thickness gauge. The film thickness can be obtained by, for example, measuring at 10 or more points and averaging the results.

[0037] <2. Method for manufacturing a connection structure>

[0038] [First Embodiment]

[0039] A method for manufacturing a connection structure related to a first embodiment comprises a connection film on a wiring board facing a chip component formed on a substrate that is transparent to laser light, a connection film on the wiring board, a connection process in which a laser light is irradiated from the substrate side to make the chip component land on the connection film, and a connection process in which the chip component and the wiring board are connected, wherein the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30°C and a frequency of 200 Hz. By doing so, the occurrence of defects such as misalignment, deformation, breakage, or detachment of the chip component during the connection process is suppressed, and the chip component can be transferred and arranged with high precision and high efficiency, thereby enabling a reduction in the tact time.

[0040] Examples of chip components include semiconductor chips, LED chips, etc., but are not particularly limited; however, the method for manufacturing a connection structure related to the present technology can be appropriately used for mass transfer in which a large number of micro-sized LED chips are mounted on a panel substrate which is a wiring board.

[0041] Hereinafter, a method for manufacturing a display device is described in which a plurality of light-emitting elements, which are LED chips, are arranged on a wiring board, which is a panel substrate, to form a light-emitting element array as a method for manufacturing a connection structure.

[0042] As a light-emitting element, a so-called flip-chip type LED having a first conductivity type electrode and a second conductivity type electrode on one side can be used. The light-emitting elements are arranged on a substrate corresponding to each subpixel constituting one pixel to form a light-emitting element array. One pixel may be composed of, for example, three subpixels of R (red), G (green), and B (blue), four subpixels of RGBW (white) and RGBY (yellow), or two subpixels of RG and GB.

[0043] Methods for arranging subpixels include, for example, stripe array, mosaic array, and delta array in the case of RGB. A stripe array arranges RGB in a vertical stripe pattern, which can achieve high precision. Additionally, a mosaic array arranges identical RGB colors diagonally, which can produce a more natural image than a stripe array. Furthermore, a delta array arranges RGB in a triangle, with each dot offset by half a pitch in each field, which can produce a natural image display.

[0044] Table 1 shows the estimated horizontal pitch between RGB, estimated chip size, and estimated electrode size for the PPI (Pixels Per Inch) when each RGB chip is arranged horizontally. The distance between chips was assumed to be at least 5 μm, and the estimated distance between RGB was set to the maximum when arranged at equal intervals. These values ​​were calculated as reference values ​​to clarify the application and examine the present technology.

[0045]

[0046] As shown in Table 1, it can be seen that up to 500 PPI is possible by making the chip size 10 × 20 μm. In addition, up to 1000 PPI is possible by making the chip size 7 × 14 μm, and more than 1000 PPI can be realized by making the chip size smaller. In addition, the chip does not necessarily have to be rectangular and may be square.

[0047] Hereinafter, with reference to FIGS. 1 to 4, a deposition process (A1) in which a light-emitting element is deposited onto an anisotropic conductive film by irradiating laser light, and a connection process (B1) in which the light-emitting element is connected to a wiring board are connected.

[0048] [Impact Process (A1)]

[0049] FIG. 1 is a cross-sectional view schematically showing a state in which a light-emitting element formed on a substrate and an anisotropic conductive film on a wiring substrate are facing each other, and FIG. 2 is an enlarged view showing the light-emitting element facing each other and a connection film on the wiring substrate. As shown in FIG. 1 and FIG. 2, first, in the impact process (A1), the chip component substrate (10) and the anisotropic conductive film (40) on the wiring substrate (30) are facing each other.

[0050] A chip component substrate (10) is provided with a substrate (11), a release material (12), and a light-emitting element (20), and a light-emitting element (30) is attached to the surface of the release material (12). The substrate (11) only needs to be transparent to laser light, and among them, it is preferable that it be quartz glass having a high light transmittance over the entire wavelength.

[0051] The release material (12) has absorption characteristics for the wavelength of the laser light and generates a shock wave by irradiating the laser light, causing the light-emitting element (20) to bounce towards the wiring substrate (30). For example, polyimide can be used as the release material (12). The thickness (T12) of the release material (12) is, for example, 1 μm or more.

[0052] The light-emitting element (20) comprises a main body (21), a first conductivity type electrode (22), and a second conductivity type electrode (23), and has a horizontal structure in which the first conductivity type electrode (22) and the second conductivity type electrode (23) are arranged on the same plane side. The main body (21) comprises a first conductivity type clad layer made of, for example, n-GaN, and, for example, In x Al y Ga 1-x-yIt has an active layer made of an N layer and a second conductivity type clad layer made of, for example, p-GaN, to have a so-called double heterostructure. A first conductivity type electrode (22) is formed in a part of the first conductivity type clad layer by a passivation layer, and a second conductivity type electrode (23) is formed in a part of the second conductivity type clad layer. When a voltage is applied between the first conductivity type electrode (22) and the second conductivity type electrode (23), carriers are concentrated in the active layer and light emission occurs through recombination.

[0053] The width (W20) of the light-emitting element (20) is, for example, 1 to 100 μm, and the thickness (T20) of the light-emitting element (20) is, for example, 1 to 20 μm.

[0054] The wiring board (30) has a first conductivity type circuit pattern and a second conductivity type circuit pattern on a substrate (31), and has a first electrode (32) and a second electrode (33) respectively at positions corresponding to, for example, the first conductivity type electrode on the p side and the second conductivity type electrode on the n side so that the light-emitting element is arranged in units of subpixels (subpixels) constituting one pixel. In addition, the wiring board (30) forms circuit patterns such as data lines and address lines of matrix wiring, for example, and enables the light-emitting element corresponding to each subpixel constituting one pixel to be turned on and off. Additionally, the wiring substrate (30) is preferably a light-transmitting substrate, the substrate (31) is preferably glass, PET (Polyethylene Terephthalate), etc., and the circuit pattern, the first electrode (32), and the second electrode (33) are preferably transparent conductive films such as ITO (Indium-Tin-Oxide), IZO (Indium-Zinc-Oxide), ZnO (Zinc-Oxide), IGZO (Indium-Gallium-Zinc-Oxide).

[0055] The anisotropic conductive film (40) contains conductive particles in a binder, and the thickness (T40) of the anisotropic conductive film (40) is, for example, 20 μm or less. In addition, the distance (D) between the light-emitting element (20) and the anisotropic conductive film (40) is preferably 10 to 1000 μm, more preferably 50 to 500 μm, and even more preferably 80 to 200 μm.

[0056] FIG. 3 is a cross-sectional view schematically showing a state in which a light-emitting element is transferred and arranged at a predetermined location on a wiring board by irradiating a laser light from the substrate side. As shown in FIG. 2 and FIG. 3, in the impact process (A1), a laser light (50) is irradiated from the substrate (11) side to transfer and arrange a light-emitting element (20) at a predetermined location on a wiring board (21).

[0057] For the transfer of the light-emitting element (20), for example, a lift (Laser Induced Forward Transfer) device may be used. The lift device comprises, for example, a telescope that makes the pulsed laser light emitted from a laser device into parallel light, a shaping optical system that uniformly shapes the spatial intensity distribution of the pulsed laser light passing through the telescope, a mask that passes the pulsed laser light shaped by the shaping optical system into a predetermined pattern, a field lens located between the shaping optical system and the mask, and a projection lens that projects the laser light passing through the pattern of the mask into a reduced size on a donor substrate, and holds the chip component substrate (10), which is the donor substrate, on a donor stage, and holds the wiring board (30), which is the receptor substrate, on a receptor stage.

[0058] As a laser device, for example, an excimer laser that emits laser light with a wavelength of 180 nm to 360 nm can be used. The oscillation wavelengths of the excimer laser are, for example, 193, 248, 308, and 351 nm, and among these oscillation wavelengths, they can be appropriately selected according to the light absorption properties of the material of the release (12).

[0059] The mask utilizes a pattern in which an array of windows of a predetermined size is formed at a predetermined pitch so that the projection at the boundary surface between the substrate (11) and the release material (12) becomes an array of desired laser light. In the mask, the pattern is formed on the substrate (11), for example, by chrome plating, and the window portions where chrome plating is not performed transmit laser light, while the portions where chrome plating is performed block laser light.

[0060] The light emitted from the laser device is incident on the telescopic optical system and propagates to the angular optical system in front of it. Just before being incident on the angular optical system, the laser light is adjusted by the telescopic optical system so that it becomes approximately parallel light at any position within the movement range of the X-axis of this donor stage, so it is always incident on the angular optical system at approximately the same size and angle (perpendicular).

[0061] The laser light passing through the shaping optical system passes through a field lens that forms an image-side telecentric reduction projection optical system in combination with a projection lens and is incident on the mask. The laser light passing through the mask pattern changes its propagation direction vertically downward by a drop mirror and is incident on the projection lens. The laser light emitted from the projection lens is incident from the side of the substrate (11) and is accurately projected at a predetermined position of the release material (12) formed on its surface (bottom surface) in a reduced size of the mask pattern.

[0062] The pulse energy of the laser light formed by imaging at the interface between the anisotropic conductive adhesive layer and the substrate is preferably 0.001 to 2 J, more preferably 0.01 to 1.5 J, and even more preferably 0.1 to 1 J. The fluence is preferably 0.001 to 2 J / cm². 2 and, more preferably 0.01 to 1 J / cm 2 and, more preferably 0.05 to 0.5 J / cm 2 The pulse width (irradiation time) is preferably 0.01 to 1 × 10⁻⁶ 9 It is picoseconds, and more preferably 0.1 to 1 × 10⁻⁶ 7 It is picoseconds, and more preferably 1 to 1 × 10⁻⁶ 5 It is a picosecond. The pulse frequency is preferably 0.1 to 10,000 Hz, more preferably 1 to 1,000 Hz, and even more preferably 1 to 100 Hz. The number of irradiation pulses is preferably 1 to 30,000,000.

[0063] By using such a lift device, a shock wave is generated on the release material (12) irradiated with laser light at the boundary surface between the substrate (11) and the release material (12), and a plurality of light-emitting elements (20) are peeled off from the substrate (11) and lifted toward the wiring board (30), and the plurality of light-emitting elements (20) can be placed at a predetermined position on the wiring board (30) with an anisotropic conductive film (40) interposed therebetween. By doing so, the occurrence of defects such as misalignment, deformation, destruction, or detachment of the light-emitting elements (20) is suppressed, and the light-emitting elements (20) can be transferred and arranged with high precision and high efficiency, thereby allowing for a reduction in tact time.

[0064] [Connection Process (B1)]

[0065] FIG. 4 is a cross-sectional view schematically showing the state in which a light-emitting element is mounted on a wiring board. As shown in FIG. 3, in the connection process (B1), a light-emitting element (20) arranged at a predetermined position on the wiring board (30) is mounted.

[0066] As a method for heat-pressing the light-emitting element (20) onto the wiring substrate (30), a connection method used in known anisotropic conductive films can be appropriately selected and used. As for the heat-pressing conditions, for example, the temperature is 120°C to 260°C, the pressure is 5 MPa to 60 MPa, and the time is 5 seconds to 300 seconds. As the anisotropic conductive film is cured, an anisotropic conductive film is formed.

[0067] According to the method for manufacturing a connection structure related to the first embodiment, the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30°C and a frequency of 200 Hz, thereby suppressing the occurrence of defects such as misalignment, deformation, breakage, or detachment of chip components during the impact process (A1), and thus allowing the chip components to be transferred and arranged with high precision and high efficiency, thereby enabling a reduction in the tact time.

[0068] [Second Embodiment]

[0069] In the first embodiment, a connection film is attached to a wiring board, but a laser light may be irradiated to transfer the connection film to a predetermined location on the wiring board, and in the impact process (A1), a chip component may be impacted onto the connection film.

[0070] That is, the method for manufacturing a connection structure related to the second embodiment comprises a transfer process in which a connection film formed on a substrate that is transparent to laser light is positioned oppositely to a wiring board and a laser light is irradiated from the substrate side to transfer a portion of the connection film onto the wiring board, a bonding process in which a chip component formed on a substrate that is transparent to laser light is positioned oppositely to a connection film on the wiring board and a laser light is irradiated from the substrate side to bond the chip component onto the portion of the connection film, and a connection process in which the chip component and the wiring board are connected, wherein the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30 ℃ and a frequency of 200 Hz.

[0071] Thus, the arrangement of the connection film can be transferred and arranged with high precision and high efficiency by irradiation with laser light. In addition, just like the first embodiment, in the impact process, the occurrence of defects such as misalignment, deformation, breakage, or detachment of chip components is suppressed, and since chip components can be transferred and arranged with high precision and high efficiency, the takt time can be shortened.

[0072] Hereinafter, with reference to FIGS. 5 to 9, a transfer process (X) for transferring and arranging an anisotropic conductive film at a predetermined location on a wiring substrate, a projecting process (A2) for projecting a light-emitting element onto the anisotropic conductive film by irradiating laser light, and a connection process (B2) for connecting the light-emitting element and the wiring substrate will be described. In addition, components identical to those of the first embodiment are given the same reference numerals, and descriptions are omitted.

[0073] [Transfer Process (X)]

[0074] FIG. 5 is a cross-sectional view schematically showing the state in which an anisotropic conductive film formed on a substrate and a wiring substrate are placed facing each other. As shown in FIG. 5, first, in the transfer process (X), the anisotropic conductive film substrate (60) and the wiring substrate (30) are placed facing each other.

[0075] An anisotropic conductive film substrate (60) comprises a substrate (61) and an anisotropic conductive film (70), wherein the anisotropic conductive film (70) is formed on the surface of the substrate (61). The substrate (61) only needs to be transparent to laser light, and among these, it is preferable that it be quartz glass having high light transmittance over the entire wavelength. Additionally, a release material may be additionally provided between the substrate (61) and the anisotropic conductive film (70).

[0076] The anisotropic conductive film (70) is preferably configured such that conductive particles are aligned in a planar direction for the sake of laser transferability. Additionally, the anisotropic conductive film (70) is preferably configured such that it has a maximum absorption wavelength, for example, at a wavelength of 180 nm to 360 nm, and an epoxy-based adhesive including high-purity bisphenol A type epoxy resin can be preferably used.

[0077] FIG. 6 is a cross-sectional view schematically showing the state in which an anisotropic conductive film is transferred and arranged at a predetermined location on a wiring board by irradiating laser light from the substrate side. As shown in FIG. 6, in the transfer process (X), laser light is irradiated from the substrate (61) side to transfer and arrange an anisotropic conductive film (70) (70a) at a predetermined location on a wiring board (30).

[0078] In the transfer process (X), it is preferable to arrange the anisotropic conductive film (70) (70a) in units of 1 pixel, and it is even more preferable to arrange them in units of subpixels constituting 1 pixel. By doing so, it is possible to accommodate light-emitting element arrays from high PPI (Pixels Per Inch) to low PPI.

[0079] In addition, the distance between the sections arranged at a predetermined position on the wiring board (30) is preferably 3 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more. In addition, the upper limit of the distance between the sections is preferably 3000 μm or less, more preferably 1000 μm or less, and even more preferably 500 μm or less. If the distance between the sections is excessively small, a method of attaching an anisotropic conductive film to the entire surface of the wiring board (20) is preferred, and if the distance between the sections is excessively large, a method of attaching an anisotropic conductive film to a predetermined position on the wiring board (30) is preferred.

[0080] For the transfer of the reorganization (70a) of the anisotropic conductive film (70), the same lift device as in the above can be used, and the anisotropic conductive film substrate (60), which is the donor substrate, is held on the donor stage, and the wiring substrate (30), which is the receptor substrate, is held on the receptor stage. The distance between the anisotropic conductive film (70) and the wiring substrate (30) is, for example, 10 to 100 μm. The oscillation wavelength of the laser device is, for example, 193, 248, 308, 351 nm, and among these oscillation wavelengths, it can be appropriately selected according to the light absorption properties of the anisotropic conductive film (70) or the material of the release material.

[0081] By using a lift device, a shock wave is generated on the anisotropic conductive film (70) irradiated with laser light at the interface between the substrate (61) and the anisotropic conductive film (70), and a plurality of fragments (70a) are peeled off from the substrate (61) and lifted toward the wiring board (30), and the plurality of fragments (70a) can be landed at a predetermined position on the wiring board (30). By doing so, the fragments (70a) of the anisotropic conductive film (70) can be transferred and arranged on the wiring board (30) with high precision and high efficiency, thereby allowing for a reduction in takt time.

[0082] The reaction rate of the reorganization (70a) of the anisotropic conductive film (70) after the transfer process (X) is preferably 25% or less, more preferably 20% or less, and even more preferably 15% or less. Since the reaction rate of the reorganization (70a) is 25% or less, it becomes possible to thermally press the light-emitting element in the connection process (B2). The reaction rate can be measured, for example, using FT-IR.

[0083] [Impact Process (A2)]

[0084] FIG. 7 is a cross-sectional view schematically showing a state in which a light-emitting element formed on a substrate and an anisotropic conductive film on a wiring substrate are facing each other, and FIG. 8 is a cross-sectional view schematically showing a state in which a light-emitting element is transferred to a predetermined position on the wiring substrate and arranged by irradiating a laser light from the substrate side.

[0085] As shown in FIG. 7, first, in the impact process (A2), the anisotropic conductive film (70a) on the chip component substrate (10) and the wiring substrate (30) are positioned facing each other. Then, as shown in FIG. 8, a laser light is irradiated from the side of the substrate (11) to transfer and arrange the light-emitting element (20) onto the anisotropic conductive film (70a) of the wiring substrate (30). For the transfer of the light-emitting element (20), a lift device may be used, for example, in the same way as in the first embodiment.

[0086] [Connection Process (B2)]

[0087] FIG. 9 is a cross-sectional view schematically showing a state in which a light-emitting element is mounted on a section arranged at a predetermined position on a wiring board. As shown in FIG. 9, in the connection process (B2), a light-emitting element (20) is mounted on a section (70a) arranged at a predetermined position on a wiring board (30). The method of heat-pressing the light-emitting element (20) onto the wiring board (30) is the same as in the first embodiment.

[0088] According to the method for manufacturing a connection structure related to the second embodiment, the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30°C and a frequency of 200 Hz, thereby suppressing the occurrence of defects such as misalignment, deformation, breakage, or detachment of chip components during the impact process (A2), and thus allowing the chip components to be transferred and arranged with high precision and high efficiency, thereby enabling a reduction in the tact time.

[0089] In addition, since the anisotropic conductive film is not present between the light-emitting elements (20) and the wiring substrate (30) is exposed, the light-emitting elements (20) can be anisotropically connected on the wiring substrate (30). Therefore, by making the wiring substrate (30) a light-transmitting substrate, excellent light transmittance can be obtained compared to the case where the anisotropic conductive film is attached to the entire surface of the wiring substrate (30).

[0090] [A variation of the second embodiment]

[0091] In the transfer process (X) of the second embodiment, laser light may be irradiated from the substrate (61) side to transfer and arrange the anisotropic conductive film (70) in electrode units of the light-emitting element. That is, the method for manufacturing a connection structure related to a modified example of the second embodiment further includes a transfer process in which a connection film formed on a substrate that is transparent to laser light is placed opposite a wiring substrate, and laser light is irradiated from the substrate side to transfer the connection film in electrode units onto the wiring substrate, and in the impact process, a chip component is impacted onto the corresponding electrode.

[0092] Thus, in a light-emitting element (20) having a horizontal structure in which the first conductivity type electrode (22) and the second conductivity type electrode (23) are arranged on the same plane side, the occurrence of a short circuit between the first conductivity type electrode (22) and the second conductivity type electrode (23) can be suppressed.

[0093] Hereinafter, with reference to FIGS. 10 to 13, a transfer process (X-1) for transferring and arranging an anisotropic conductive film at a predetermined location on a wiring substrate, a projecting process (A2-1) for projecting a light-emitting element onto the anisotropic conductive film by irradiating laser light, and a connection process (B2-1) for connecting the light-emitting element and the wiring substrate will be described. In addition, components identical to those of the second embodiment are given the same reference numerals, and their descriptions are omitted.

[0094] [Transfer Process (X-1)]

[0095] First, in the transfer process (X-1), the anisotropic conductive film substrate (60) and the wiring substrate (30) are placed facing each other, as shown in FIG. 5, in the same way as in the second embodiment and the transfer process (X).

[0096] FIG. 10 is a cross-sectional view schematically showing the state in which an anisotropic conductive film is transferred and arranged in electrode units on a wiring substrate by irradiating laser light from the substrate side. As shown in FIG. 10, in the transfer process (X-1), laser light is irradiated from the substrate (61) side to transfer and arrange the anisotropic conductive film (70) (72, 73) in electrode units on a wiring substrate (30).

[0097] In the transfer process (X-1), the anisotropic conductive film (70) is transferred (72, 73) to the first electrode (32) and the second electrode (33), respectively, corresponding to the first conductive electrode (22) and the second conductive electrode (23) of the light-emitting element (20), and arranged. By transferring and arranging the transfer (72, 73) only to the first electrode (32) and the second electrode (33), the occurrence of a short circuit between the first conductive electrode (22) and the second conductive electrode (23) can be suppressed.

[0098] For the transfer of the anisotropic conductive film (70) and the reorganization (72, 73), the same lift device as described above can be used, and the reorganization (72, 73) of the anisotropic conductive film (70) can be transferred and arranged on the wiring substrate (30) in electrode units with high precision and high efficiency, thereby allowing for a reduction in takt time.

[0099] The reaction rate of the reshaping (72, 73) of the anisotropic conductive film (70) after the transfer process (X-1) is, as in the second embodiment and the transfer process (X), preferably 25% or less, more preferably 20% or less, and even more preferably 15% or less. Since the reaction rate of the reshaping (70a) is 25% or less, it becomes possible to thermally press the light-emitting element in the connection process (B2-1). The reaction rate can be measured, for example, using FT-IR.

[0100] [Impact Process (A2-1)]

[0101] FIG. 11 is a cross-sectional view schematically showing a state in which a light-emitting element formed on a substrate and a structure transferred and arranged in electrode units on a wiring substrate are facing each other, and FIG. 12 is a cross-sectional view schematically showing a state in which a laser light is irradiated from the substrate side to strike the light-emitting element onto a structure on a corresponding electrode and arranged.

[0102] As shown in FIG. 11, first, in the impact process (A2-1), the chip component substrate (10) and the wiring substrate (30) are placed facing each other, and the first conductivity type electrode (22) and the second conductivity type electrode (23) of the light-emitting element (20) formed on the chip component substrate (10) are aligned with the remodels (72, 73) transferred onto the first electrode (32) and the second electrode (33), respectively. Then, as shown in FIG. 12, a laser light is irradiated from the side of the substrate (11) to impact the light-emitting element (20) onto the remodels (72, 73) on the corresponding electrodes. For the transfer of the light-emitting element (20), a lift device may be used, for example, in the same way as in the first embodiment.

[0103] [Connection Process (B2-1)]

[0104] FIG. 13 is a cross-sectional view schematically showing a state in which a light-emitting element is mounted on a reorganized wiring board. As shown in FIG. 13, in the connection process (B2-1), a light-emitting element (20) transferred to the wiring board (30) is mounted. The method of heat-pressing the light-emitting element (20) onto the wiring board (30) is the same as in the first embodiment.

[0105] According to the method for manufacturing a connection structure related to the modification of the second embodiment, the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30°C and a frequency of 200 Hz, thereby suppressing the occurrence of defects such as misalignment, deformation, breakage, or detachment of chip components during the impact process (A22-1), and thus allowing the chip components to be transferred and arranged with high precision and high efficiency, thereby enabling a reduction in the tact time.

[0106] In addition, since there is no anisotropic conductive film between the first conductive electrode (22) and the second conductive electrode (23) of the light-emitting element (20) and the wiring substrate (30) is exposed, the light-emitting element (20) can be anisotropically connected on the wiring substrate (30), so short circuits can be suppressed compared to the case where the anisotropic conductive film is attached across the first conductive electrode (22) and the second conductive electrode (23).

[0107] [Third Embodiment]

[0108] In the second embodiment, the connection film is transferred to a predetermined location on the wiring board by irradiating with laser light, but the connection film may be formed on the electrode of the chip component in advance.

[0109] That is, the method for manufacturing a connection structure related to the third embodiment comprises a connection film on the electrode surface of a chip component formed on a substrate having transmittance to laser light and a wiring board facing each other, a laser light irradiated from the substrate side to cause the chip component to be impacted onto the wiring board with the connection film interposed therebetween, and a connection process for connecting the chip component and the wiring board, wherein the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30 ℃ and a frequency of 200 Hz.

[0110] Thus, just like in the first embodiment, in the impact process, the occurrence of defects such as misalignment, deformation, breakage, or detachment of chip components can be suppressed, and chip components can be transferred and arranged with high precision and high efficiency, thereby enabling a reduction in takt time.

[0111] Hereinafter, with reference to FIG. 14, a firing process (A3) in which a light-emitting element is fired onto a portion of an anisotropic conductive film by irradiating laser light, and a connection process (B3) in which a light-emitting element is connected to a wiring board are described. In addition, the same reference numerals are given to components identical to those in the first and second embodiments, and their descriptions are omitted.

[0112] [Impact Process (A3)]

[0113] FIG. 14 is a cross-sectional view schematically showing a state in which a connection film formed on the electrode surface of a light-emitting element and a wiring substrate are placed facing each other. As shown in FIG. 14, first, in the impact process (A3), a chip component substrate (10) and a wiring substrate (30) are placed facing each other. An anisotropic conductive film (80) is formed on the electrode surface of the light-emitting element (20), and the distance between the anisotropic conductive film (80) and the wiring substrate (30) is, for example, 10 to 100 μm.

[0114] The method of forming an anisotropic conductive film (80) on the electrode surface of a light-emitting element (20) is not particularly limited, but, for example, as in the transfer process (X) of the second embodiment, an anisotropic conductive film formed on a substrate that is transparent to laser light may be positioned opposite the electrode surface of the light-emitting element, and laser light may be irradiated from the substrate side to transfer the anisotropic conductive film onto the electrode surface of the light-emitting element.

[0115] Next, a laser light is irradiated from the substrate (11) side to transfer and arrange the light-emitting element (20) onto the wiring substrate (30) via an anisotropic conductive film (80). For the transfer of the light-emitting element (20), a lift device may be used, for example, in the same way as in the first embodiment.

[0116] [Connection Process (B3)]

[0117] In the connection process (B3), a light-emitting element (20) arranged at a predetermined position on the wiring board (30) is mounted. The method of heat-pressing the light-emitting element (20) onto the wiring board (30) is the same as in the first embodiment.

[0118] According to the method for manufacturing a connection structure related to the third embodiment, the connection film contains a rubber component, has a durometer A hardness of 20 to 40, and has a storage modulus of 60 MPa or less at a temperature of 30°C and a frequency of 200 Hz, thereby suppressing the occurrence of defects such as misalignment, deformation, breakage, or detachment of chip components during the impact process (A3), and thus allowing the chip components to be transferred and arranged with high precision and high efficiency, thereby enabling a reduction in the tact time.

[0119] In addition, since the anisotropic conductive film is not present between the light-emitting elements (20) and the wiring substrate (30) is exposed, the light-emitting elements (20) can be anisotropically connected on the wiring substrate (30). Therefore, by making the wiring substrate (30) a light-transmitting substrate, excellent light transmittance can be obtained compared to the case where the anisotropic conductive film is attached to the entire surface of the wiring substrate (30).

[0120] Examples

[0121] <3. First Embodiment>

[0122] In the first embodiment, a chip component formed on quartz glass and a connection film on a glass substrate were positioned facing each other, and a laser light was irradiated from the substrate side to deposit the chip component onto the connection film. Furthermore, the present embodiment is not limited to these.

[0123] [Production of the Connection Film]

[0124] The following materials were prepared.

[0125] Phenoxy Resin (Product Name: PKHH, Manufactured by Tomoe Chemical Industry Co., Ltd.)

[0126] High-purity Bisphenol A type epoxy resin (Product name: YL-980, manufactured by Mitsubishi Chemical Corporation)

[0127] Hydrophobic silica (Product name: R2O2, manufactured by Nippon Aerosil Co., Ltd.)

[0128] Acrylic Rubber (Product Name: SG80H, Manufactured by Nagase Chemtex Co., Ltd.)

[0129] Cathionic polymerization initiator (Product name: SI-60L, manufactured by Sanshin Chemical Industry Co., Ltd.)

[0130] delete

[0131] Conductive particles (average particle size 2.2 μm, resin core metal-coated fine particles, Ni plating thickness 0.2 μm, manufactured by Sekisui Chemical Industry Co., Ltd.)

[0132] As shown in Table 2, each material was blended in a predetermined mass portion to prepare a resin layer of a predetermined thickness on a glass substrate with a thickness of 0.5 mm. Conductive particles from the obtained resin layer were prepared by the method described in Japanese Patent No. 6187665 such that the conductive particles approximately coincided with the interface of one side of the resin layer, with a particle face density of 58,000 pcs / mm². 2 Connecting films 1 to 5 were produced by aligning them so as to be. The connecting film (6) was made by thermoforming acrylic rubber onto a glass substrate.

[0133] [Measurement of rubber hardness of connection film]

[0134] In accordance with JIS K 6253, rubber hardness (Japanese Industrial Standard JIS-A hardness) was measured using Durometer A.

[0135] [Measurement of Storage Modulus of Connection Film]

[0136] Dynamic viscoelasticity testing was performed using an indentation test device (iMicro type nanoindenter manufactured by KLA). Using a flat punch with a diameter of 100 μm, the target indentation depth was set to 1 μm, and the storage modulus was measured at a temperature of 30°C and a frequency of 200 Hz by sweeping in a frequency range of 1 to 200 Hz. The Poisson ratio of the sample was set to 0.5, and the average value of the 12 measurement points of each sample was calculated.

[0137] [Measurement of storage modulus of connection film after curing]

[0138] For the connection film after curing, the storage modulus at a temperature of 30°C in tensile mode was measured using a viscoelastic tester (vibron) in accordance with JIS K7244. The measurement conditions were a frequency of 11 Hz and a heating rate of 3°C / min.

[0139]

[0140] [Transfer of chip components]

[0141] Using a list device (MT-30C200), a chip component formed on quartz glass was deposited onto a connection film on a glass substrate. A release material (polyimide) was formed between the quartz glass and the chip component using a TEG (Test Element Group).

[0142] As described above, the list device comprises a telescope that makes the pulsed laser light emitted from the laser device into parallel light, a shaping optical system that uniformly shapes the spatial intensity distribution of the pulsed laser light passing through the telescope, a mask that passes the pulsed laser light shaped by the shaping optical system into a predetermined pattern, a field lens located between the shaping optical system and the mask, and a projection lens that projects the laser light passing through the pattern of the mask into a reduced size on a donor substrate, a quartz substrate on which a chip component, which is the donor substrate, is held by a release material is held on a donor stage, a glass substrate on which a connection film, which is the receptor substrate, is attached is held on a receptor stage, and the distance between the chip component and the connection film is set to 100 μm.

[0143] The laser device used an excimer laser with an oscillation wavelength of 248 nm. The pulse energy of the laser light was 600 J, and the fluence was 150 J / cm². 2 The pulse width (irradiation time) was 30,000 picoseconds, the pulse frequency was 0.01 kHz, and the number of irradiation pulses was set to 1 pulse per ACF1 subpiece. The pulse energy of the laser light formed at the interface between the anisotropic conductive adhesive layer and the substrate was 0.001 to 2 J, and the fluence was 0.001 to 2 J / cm². 2 and the pulse width (irradiation time) is 0.01 to 1 × 10⁻⁶ 9 It was picoseconds, the pulse frequency was 0.1 to 10000 Hz, and the number of irradiation pulses was 1 to 30,000,000.

[0144] The mask used a pattern in which an array of windows of a predetermined size at a predetermined pitch was formed so that the projection at the interface between the quartz glass, which is the donor substrate, and the release material is 30 × 50 μm in the shape of the chip component.

[0145] [Evaluation of Impact]

[0146] Table 3 shows the evaluation results of chip component transfer on connection films 1 to 6. A total of 100 chip components were transferred onto the connection films, and the number of chip components that landed normally on the connection films was counted using a microscope. The evaluation of the impact was based on the ratio of chip components that landed normally, using the following judgments A to D. A judgment of C or higher is desired.

[0147] A : 100 %

[0148] B: 98% or more and less than 100%

[0149] C: 90% or more and less than 98%

[0150] D: Less than 90%

[0151]

[0152] As shown in Table 3, the transfer rate of the chip component was less than 90% because the durometer A hardness of the connection film (4) was excessively high and the durometer A hardness of the connection film (5) was excessively low. On the other hand, the connection films (1 to 3, 6) had a durometer A hardness of 20 to 40 and a storage modulus of 60 MPa or less at a temperature of 30°C and a frequency of 200 Hz, so the transfer rate of the chip component could be made 90% or more.

[0153] <4. Second Example>

[0154] In the second embodiment, the chip component and the wiring board were heat-pressed using the connection film (1 to 6) of the first embodiment. Furthermore, the present embodiment is not limited to these.

[0155] [Creation of Connection Structure]

[0156] In the same manner as in the first embodiment, a chip component was deposited onto a connection film of a wiring board and a connection structure was fabricated by heat pressing under conditions of a temperature of 150°C - a pressure of 30 MPa - a time of 30 sec. For the chip component (outer shape 50 μm × 50 μm, thickness 150 μm), a TEG (Test Element Group) having a pair of electrodes (Cr / Au-plated bump 10 μm × 10 μm) formed on the chip component was used. For the wiring board, a glass substrate (thickness 0.5 mm, Ti / Al / Ti pattern 10 μm × 10 μm) was used.

[0157] [Evaluation of the orthodox nature]

[0158] Table 4 shows the evaluation results of the conductivity of the connection films (1 to 6).

[0159] Conductivity was measured through the conductive wiring on the wiring board side. Conductivity was evaluated based on the resistance value using the following judgments A to D. A judgment of C or higher is desired.

[0160] A: 50 Ω or less

[0161] B: Over 50 Ω and up to 100 Ω

[0162] C: Over 100 Ω and up to 200 Ω

[0163] D: Over 200 Ω

[0164]

[0165] As shown in Table 4, since the connection film (6) is not heat-cured, it has poor conductivity and requires research such as forming connection parts such as solder bumps on the chip components. Meanwhile, the connection films (1 to 5) were able to obtain good conductivity with a storage modulus of 2000 MPa or more, which exceeds 100 MPa or more when measured in tensile mode after curing. Explanation of the symbols

[0166] 10: Chip component board 11 : Entry 12 : Release material 20 : Light-emitting element 21 : Main body 22: First conductivity type electrode 23 : Second conductivity type electrode 30: Wiring board 31 : Entry 32: First electrode 33: Second electrode 40: Anisotropic Challenge Film 50 : Laser light 60: Anisotropic conductive film substrate 61 : Entry 70: Anisotropic Challenge Film 70a : Reorganization 72 : Reorganization 73 : Reorganization 80: Anisotropic Challenge Film 101 : LED 102 : Transfer material 103 : Stamp material 104 : Panel Substrate 105 : Connection film 111 : LED 112 : Transfer material 113 : Release material 114 : Panel board 115 : Connection film

Claims

Claim 1 A connecting film comprising a film-forming resin, a thermosetting resin, a curing agent, an inorganic filler, and a rubber component, wherein the content of the rubber component is 1 to 20 parts by mass per 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component, and the content of the inorganic filler is 5 to 15 parts by mass per 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component, the durometer A hardness before curing is 20 to 40, and the storage modulus before curing is 60 MPa or less at a temperature of 30 ℃ and a frequency of 200 Hz of a dynamic viscoelasticity test using an indentation test device. Claim 2 A connection film according to claim 1, wherein the storage modulus at a temperature of 30°C measured in a tensile mode in accordance with JIS K7244 after curing is 0.1 GPa or higher. Claim 3 A connection film according to claim 1, further comprising conductive particles, wherein the conductive particles are aligned in a planar direction. Claim 4 A connecting film according to claim 1, wherein the rubber component is acrylic rubber. Claim 5 A connecting film according to claim 1, wherein the thermosetting resin comprises an epoxy compound and the curing agent is a cation polymerization initiator. Claim 6 A connecting film according to claim 1, wherein the content of the rubber component is 2 to 10 parts by mass per 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component, and the content of the inorganic filler is 8 to 12 parts by mass per 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component. Claim 7 A connection film characterized by being used in a laser-based chip placement method in claim 1. Claim 8 A connection film substrate having a connection film described in any one of claims 1 to 7 and a substrate having transmittance to laser light. Claim 9 In claim 8, a connection film substrate further comprising a release material between the connection film and the substrate. Claim 10 A chip component formed on a substrate having transmittance to laser light and a connection film on a wiring board are positioned oppositely, and a laser light is irradiated from the substrate side to deposit the chip component onto the connection film; the connection process comprises depositing the chip component and the wiring board, wherein the connection film contains a film-forming resin, a thermosetting resin, a curing agent, an inorganic filler, and a rubber component, wherein the content of the rubber component is 1 to 20 parts by mass per 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component, and the content of the inorganic filler is 5 to 15 parts by mass per 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component, and wherein the connection film has a durometer A hardness of 20 to 40 before curing, a temperature of 30 ℃, and a frequency A method for manufacturing a connection structure having a storage modulus of 60 MPa or less before curing at 200 Hz. Claim 11 A method for manufacturing a connection structure according to claim 10, wherein a connection film formed on a substrate having transmittance to laser light and a wiring board are positioned opposite each other, and a laser light is irradiated from the substrate side to transfer a portion of the connection film onto the wiring board, and wherein in the impact process, the chip component is impacted onto the portion of the connection film. Claim 12 A method for manufacturing a connection structure according to claim 10, wherein a connection film formed on a substrate having transmittance to laser light and a wiring board are positioned opposite each other, and a laser light is irradiated from the substrate side to transfer the arrangement of the connection film onto the wiring board in electrode units, and wherein in the impact process, the chip component is impacted onto the arrangement of the corresponding electrode. Claim 13 A connection film on the electrode surface of a chip component formed on a substrate having transmittance to laser light and a wiring board are positioned opposite each other, and a laser light is irradiated from the substrate side to deposit the chip component onto the wiring board with the connection film interposed therebetween; a connection process for connecting the chip component and the wiring board, wherein the connection film contains a film-forming resin, a thermosetting resin, a curing agent, an inorganic filler, and a rubber component, wherein the content of the rubber component is 1 to 20 parts by mass per 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component, and the content of the inorganic filler is 5 to 15 parts by mass per 100 parts by mass of the total of the film-forming resin, the thermosetting resin, the curing agent, the inorganic filler, and the rubber component, and wherein the connection film has a durometer A hardness of 20 to 40 A method for manufacturing a connection structure having a storage modulus of 60 MPa or less before curing at a temperature of 30 ℃ and a frequency of 200 Hz.

Citation Information

Patent Citations

  • Optically Transparent Hot Melt Adhesives and Their Use

    JP2017531057A

  • Adhesive composition for electronic part and adhesive film comprising the same

    KR1020110137861A

  • Anisotropic conductive film and method for producing connection structure

    KR1020130027436A

  • adhesive tape

    KR1020200143215A